Security Issues and Outcomes of the 2015 General Elections in North Eastern Nigeria - Gar, Ruqayya, Aminu (My University, 2022)
Security issues have the propensity to stimulate electorates to adopt positive democratic attitudes that can facilitate safety. Such as following and engaging approaches that proffers a sense of safety, self value and cause the aspiration for leaders who share these common goals. Studies of security and elections in north eastern Nigeria exist however, limited to academic standards. This study examines security issues and factors influencing the outcome of the 2015 general elections in north eastern Nigeria through a qualitative method of data collection and analysis. The study concludes that factors, that caused the victory of an opposition political party, the All Progressives Congress (APC) in the 2015 general elections includes. The electorates’ evaluations of the Peoples Democratic Party (PDP) government’s depressing records in securing lives and property, mismanagement of the economy, and challenges in confronting corruption; better election campaign tactics and credible candidates presented by opposition parties; and better preparation by the electoral body, particularly the use of biometric voter cards. But most importantly of the factors is insurgency that occupied the northeast region. This shows the relevance of security, economy, and political concerns as top factors influencing electoral outcomes in north eastern, Nigeria.
Keywords: Bauchi; Elections; Failure; Peoples Democratic Party; Security Issues